Long-term changes in cognitive status of patients with type 2 diabetes mellitus after coronary artery bypass graft surgery - A. S. Sosnina; I. V. Tarasova; I. D. Syrova; O. V. Maleva; O. A. Trubnikova; O. L. Barbarash (Фундаментальная и клиническая медицина)
Aim. To study long-term changes (5 to 7 years after coronary artery bypass graft (CABG) surgery) in cognitive status of patients with type 2 diabetes.Materials and Methods. The study included 47 male patients admitted to the Research Institute for Complex Issues of Cardiovascular Diseases for the CABG surgery. Criteria of inclusion were signed informed consent, age from 40 to 75 years, male gender, planned on-pump CABG surgery, and right-handedness. Criteria of exclusion were brain pathology at multislice computed tomography, chronic cerebral ischemia grade II-IV, Beck Depression Inventory score > 16 points, the Mini-Mental State Examination (MMSE) score < 24 points and the Frontal Assessment Battery score < 11 points, arrhythmia, class IIB-IV chronic heart failure stage IIB, chronic obstructive pulmonary disease, cancer, and past medical history of brain injury or stroke. Pre-operative examination of patients classified them into two groups: with (n = 21) and without (n = 26) type 2 diabetes mellitus (DM).Results. 5-7 years after CABG surgery, patients with type 2 DM had a cognitive decline according to MMSE scale as compared to the preoperative level (28,0 [27,0; 29,0] and 27,0 [26,0; 28,0], p = 0.04). In keeping with these findings, odds ratio (OR) of mild cognitive impairment (MCI) in patients with type 2 DM was 1.92 (95% CI = 1.09- 3.37, p = 0.02). Psychomotor and executive functions were reduced in patients with type 2 DM both at baseline and in particular 5-7 years after CABG (p ≤ 0.05). The correlation between glycated hemoglobin (HbA1c) and cognitive parameters were found only in patients with type 2 DM. Higher HbA1c level was also associated with deteriorated executive functions and short-term memory.Conclusion. 5−7 years after CABG surgery, patients with type 2 DM suffer from a cognitive decline and reduced psychomotor and executive functions.